Identification of proteomic landscape of drug-binding proteins in live cells by proximity-dependent target ID. Issue 12 (15th December 2022) - Kwak, Chulhwan; Park, Cheolhun; Ko, Minjeong; Im, Chun Young; Moon, Heegyum; Park, Young-Hoon; Kim, So Young; Lee, Seungyeon; Kang, Myeong-Gyun; Kwon, Ho Jeong; Hong, Eunmi; Seo, Jeong Kon; et al.
Summary: Direct identification of the proteins targeted by small molecules can provide clues for disease diagnosis, prevention, and drug development. Despite concentrated attempts, there are still technical limitations associated with the elucidation of direct interactors. Herein, we report a target-ID system called proximity-based compound-binding protein identification (PROCID), which combines our direct analysis workflow of proximity-labeled proteins (Spot-ID) with the HaloTag system to efficiently identify the dynamic proteomic landscape of drug-binding proteins. We successfully identified well-known dasatinib-binding proteins (ABL1, ABL2) and confirmed the unapproved dasatinib-binding kinases (e.g., BTK and CSK) in a live chronic myeloid leukemia cell line. PROCID also identified the DNA helicase protein SMARCA2 as a dasatinib-binding protein, and the ATPase domain was confirmed to be the binding site of dasatinib using a proximity ligation assay (PLA) and in cellulo biotinylation assay. PROCID thus provides a robust method to identify unknown drug-interacting proteins in live cells that expedites the mode of action of the drug. Graphical abstract: Highlights: A target-ID method (PROCID) was developed based on proximity labeling PROCID reveals dasatinib- and SAHA-binding proteins in live cells SMARCA2, a core BAF complex ATPase, is revealed as a dasatinib-binding protein Abstract : Kwak et al. developed a proximity-dependent target-ID system (PROCID) that identifies the proteomic landscape of drug-binding proteins in live cells. This system revealed dasatinib-binding proteins, including SMARCA2, and SAHA-binding proteins. These findings will contribute to the deeper understanding of the modes of action of diverse drugs.